Patterns and Determinants of Adoption of High Yielding Varieties: Farm-level Evidence from Bangladesh (The Pakistan Development Review, 1988)
Observations u5mg Bangladeshi survey data tend to support Ahmed's (1981) and Asaduzuman's (1979) hypothesis postulating an inverse relationship between farm size and intensity of adoption but not Jones' (1984) U-shaped relationship. However, since farm size alone is an inadequate predictor of HYV adoption, bivariate and multivariate technique including discriminant analysis are used to identify influences on HYV adoption of such variables as subsistence pressure, tenancy, labour scarcity, education, availability of irrigation. Irrigation emerges as the key determinant of HYV adoption.